Anti-Inflammatory Effect of Tacrolimus/Hydroxypropyl-β-Cyclodextrin Eye Drops in an Endotoxin-Induced Uveitis Model - Xurxo García-Otero; Cristina Mondelo-García; Francisco González; Roman Perez-Fernandez; Leandro Avila; Jose Ramón Antúnez-López; Miguel González-Barcia; Alfredo Adan; Pablo Aguiar; Francisco J. Otero-Espinar; Maria A. Bermúdez; Anxo Fernández-Ferreiro (Pharmaceutics, 2021)
Background: Uveitis is an infrequent disease which constitutes a major cause of ocular morbidity. Correct management is essential, being corticosteroids its cornerstone. In case of contraindication to corticosteroids or treatment failure, the use of topical tacrolimus (TAC) could be an alternative which has already demonstrated safety and effectiveness in other ocular pathologies. However, TAC eye drops are not marketed, thus their elaboration must be carried out in Hospital Pharmacy Departments (HPDs). Methods: 32 Sprague-Dawley rats were divided into 4 groups of 8 rats each: (a) untreated healthy rats (Healthy); (b) untreated Endotoxin-Induced Uveitis model-rats (EIU); (c) EIU-rats treated with standard treatment of dexamethasone ophthalmic drops (DXM) and (d) EIU-rats treated with TAC-hydroxypropyl-β-cyclodextrin eye drops previously developed by our group (TAC-HPβCD). The mRNA expression levels of IL-6, IL-8, MIP-1α and TNF-α, quantitative analysis of leucocytes in aqueous humor and histological evaluation were performed. Results: TAC-HPβCD eye drops demonstrated to reduce ocular inflammation, expression of IL-6, TNF-α, MIP-1α and leukocyte infiltration in aqueous humor. Conclusions: TAC-HPβCD eye drops showed beneficial effect in EIU model in rats, positioning as an alternative for uveitis treatment in case of corticosteroids resistance or intolerance.